Pancreatic Metastasis from Colon Carcinoma: A Case Report - Vaccari, Samuele; Mirarchi, Mariateresa; De Raffele, Emilio; Palumbo, Silvia; Cola, Bruno (JOP. Journal of the Pancreas, 2013)
Context The pancreas is an uncommon location for metastases from other primary cancers; in particular, lesions from colorectal cancer account for 1.7% of all metastases. Due to their rarity, the role of surgery in these patients is not yet clear, even though pancreatic resection is considered for isolated pancreatic metastases. The interval between colorectal surgery and pancreatic metastasis is usually short, and an interval of more than five years is exceptional. We present a patient previously operated for an adenocarcinoma of the left colon and metachronous liver metastases who developed a tumor of the pancreas during the follow-up, seven years after colon resection. To our knowledge, this is the first reported case of pancreatic resection after colon and liver resections. Case report On March 2005, an adenocarcinoma of the left colon was diagnosed in a 67-year-old male: he received left hemicolectomy (pT3N1,G2) followed by adjuvant chemotherapy. In June 2006 metachronous colorectal liver metastases were diagnosed and the patient underwent right hepatectomy. In October 2008 liver metastases recurred and he received subsegmentectomy S3. From February to October 2009 a FOLFOX based chemotherapy was performed. He was regularly monitored with CT scans of the chest and abdomen, tumor markers and colonoscopy. In January 2012 a CT scan of the abdomen showed a lesion of 26x18 mm in diameter of the tail of the pancreas, confirmed by subsequent 18FDG PET-TC. Colonoscopy was negative for recurrence of the primary disease. No other lesion was detected. A ultrasonography-guided distal splenopancreatectomy was performed. The postoperative course was characterized by the appearance of a low-flow pancreatic fistula which was treated conservatively. The patient was discharged on 16th postoperative day. Histological examination of the surgical specimen demonstrated a metastatic adenocarcinoma of the colon. Conclusion Colorectal metastases to the pancreas are rare, but should be suspected in patients followed for colorectal malignancies. Pancreatic resection can be suggested in selected patients, but it should be deserved to experienced centers, especially in case of iterative abdominal surgery before pancreatic resection.